Development and Pilot Testing of Multimedia Patient Education Tools for Patients with Knee Osteoarthritis, Osteoporosis, and Rheumatoid Arthritis - Lopez-Olivo, Maria A. (Arthritis Care Res (Hoboken), 2017)
BACKGROUND: We developed and tested multimedia patient education tools (video tools) for patients with knee osteoarthritis (OA), osteoporosis (OP) and rheumatoid arthritis (RA). METHODS: We followed an “edutainment” model, incorporating educational patient story lines. The goals were designed to make the programs both didactic and entertaining, with navigation and graphical user interfaces as simple as possible. We created both English and Spanish-language versions. Once the video tool was finalized, 60 patients, 20 per disease, were shown the tool and were interviewed. Disease knowledge was our primary outcome and decision conflict, disease management, and acceptability were secondary outcomes. RESULTS: We observed statistically significant differences in pre-post knowledge questionnaire scores (before and after viewing the video tool) (OA, p=0.03; OP, p=0.001; RA, p<0.0001). Most participants felt they: 1) gained “clarity” on disease duration, symptoms, and time medication takes to start acting, 2) were “encouraged to see their doctor regularly”, and 3) were more aware about taking their medications. In terms of acceptability, most patients in all disease groups found the length and amount of information presented in the video tools to be “just right”, and the presentation as ‘balanced”. In terms of comprehension, all participants provided a favorable evaluation of the video tool; all found the video easy to use, the vocabulary easy to understand, and the materials be well organized. CONCLUSIONS: Multimedia tools that incorporate videos may help patients better understand and manage their disease. Patient involvement in the development process is essential to ensure relevant content and usability.